Trends in secondary inorganic aerosol pollution in China and its responses to emission controls of precursors in wintertime - F. Meng; Y. Zhang; J. Kang; M. R. Heal; S. Reis; S. Reis; S. Reis; M. Wang; L. Liu; K. Wang; S. Yu; P. Li; et al. (Atmospheric Chemistry and Physics, 2022)
The Chinese government recently proposed ammonia (NH3) emission reductions (but without a specific national target) as a strategic option to mitigate fine particulate matter (PM2.5) pollution. We combined a meta-analysis of nationwide measurements and air quality modeling to identify efficiency gains by striking a balance between controlling NH3 and acid gas (SO2 and NOx) emissions. We found that PM2.5 concentrations decreased from 2000 to 2019, but annual mean PM2.5 concentrations still exceeded 35 µg m−3 at 74 % of 1498 monitoring sites during 2015–2019. The concentration of PM2.5 and its components were significantly higher (16 %–195 %) on hazy days than on non-hazy days. Compared with mean values of other components, this difference was more significant for the secondary inorganic ions SO<msubsup>42-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="13pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="6181d6711c50a62cc80d469e7dc67eab"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-6291-2022-ie00001.svg" width="13pt" height="17pt" src="acp-22-6291-2022-ie00001.png"/></svg:svg>, NO<msubsup>3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="9pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="ee54bb0fff66afdafaf51bed1fde360d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-6291-2022-ie00002.svg" width="9pt" height="16pt" src="acp-22-6291-2022-ie00002.png"/></svg:svg>, and NH<msubsup>4+</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="f1ca5762abf079d28af10bf21d382d4c"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-6291-2022-ie00003.svg" width="8pt" height="15pt" src="acp-22-6291-2022-ie00003.png"/></svg:svg> (average increase 98 %). While sulfate concentrations significantly decreased over this period, no significant change was observed for nitrate and ammonium concentrations. Model simulations indicate that the effectiveness of a 50 % NH3 emission reduction for controlling secondary inorganic aerosol (SIA) concentrations decreased from 2010 to 2017 in four megacity clusters of eastern China, simulated for the month of January under fixed meteorological conditions (2010). Although the effectiveness further declined in 2020 for simulations including the natural experiment of substantial reductions in acid gas emissions during the COVID-19 pandemic, the resulting reductions in SIA concentrations were on average 20.8 % lower than those in 2017. In addition, the reduction in SIA concentrations in 2017 was greater for 50 % acid gas reductions than for the 50 % NH3 emission reductions. Our findings indicate that persistent secondary inorganic aerosol pollution in China is limited by emissions of acid gases, while an additional control of NH3 emissions would become more important as reductions of SO2 and NOx emissions progress.